Fixational eye movements and binocular vision - Otero-Millan, Jorge; Macknik, Stephen L.; Martinez-Conde, Susana (Frontiers in Integrative Neuroscience, 2014)
During attempted visual fixation, small involuntary eye movements –called fixational eye movements–continuously change of our gaze’s position. Disagreement between the left and right eye positions during such motions can produce diplopia (double vision). Thus, the ability to properly coordinate the two eyes during gaze fixation is critical for stable perception. For the last 50 years, researchers have studied the binocular characteristics of fixational eye movements. Here we review classical and recent studies on the binocular coordination (i.e. degree of conjugacy) of each fixational eye movement type: microsaccades, drift and tremor, and its perceptual contribution to increasing or reducing binocular disparity. We also discuss how amblyopia and other visual pathologies affect the binocular coordination of fixational eye movements.